Alloprevotella rava isolated from a mixed infection of an elderly patient with chronic mandibular osteomyelitis mimicking oral squamous cell carcinoma. (July 2021) - Ulger Toprak, N.; Duman, N.; Sacak, B.; Ozkan, M.C.; Sayın, E.; Mulazimoglu, L.; Soyletir, G.
Abstract: The anaerobic, Gram-negative bacillus Alloprevotella rava has recently been described in the human oral cavity. To our knowledge, this species has not been isolated from chronic osteomyleitis samples. We present the first case of A. rava infection in a 92-year-old woman with polymicrobial chronic mandibular osteomyelitis, mimicking oral squamous cell carcinoma.